1990
DOI: 10.1002/cne.902960308
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the medial cerebellar nucleus to oculomotor‐related midbrain areas in the rat: An anterograde and retrograde HRP study

Abstract: The mesencephalic projections of the medial cerebellar nucleus (MCN) were studied in the rat by using the method of anterograde transport of wheat germ agglutinin/horseradish peroxidase to establish connections of the nucleus with oculomotor-related nuclei as a basis for its proposed role in eye movement. The principal targets of projections were the supraoculomotor ventral periaqueductal gray (PAG) and lateral PAG, and paraoculomotor cell groups (nucleus of Darkschewitsch and medial accessory nucleus of Becht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In respect to cerebellar-PAG projections, Whiteside and Snider (1953) showed that electrical stimulation of vermal lobule VII in the anesthetized cat can evoke responses in the dorsal PAG with two distinct latencies (2–3 ms and 8–12 ms), which raises the possibility that multiple cerebello-PAG pathways exist. Consistent with a direct (short latency) projection, anatomical tracing studies have shown the existence of efferent fastigial projections to the PAG in a number of species (Martin et al (1974) in the opossum; Beitz (1982); Gonzalo-Ruiz and Leichnetz (1987), Gonzalo-Ruiz et al (1990) and Teune et al (2000) in the rat, and Gonzalo-Ruiz et al (1988) in monkey). Many of these studies have advanced the view that the projections subserve an oculomotor function.…”
Section: Cerebellar Output To Survival Circuitsmentioning
confidence: 80%
“…In respect to cerebellar-PAG projections, Whiteside and Snider (1953) showed that electrical stimulation of vermal lobule VII in the anesthetized cat can evoke responses in the dorsal PAG with two distinct latencies (2–3 ms and 8–12 ms), which raises the possibility that multiple cerebello-PAG pathways exist. Consistent with a direct (short latency) projection, anatomical tracing studies have shown the existence of efferent fastigial projections to the PAG in a number of species (Martin et al (1974) in the opossum; Beitz (1982); Gonzalo-Ruiz and Leichnetz (1987), Gonzalo-Ruiz et al (1990) and Teune et al (2000) in the rat, and Gonzalo-Ruiz et al (1988) in monkey). Many of these studies have advanced the view that the projections subserve an oculomotor function.…”
Section: Cerebellar Output To Survival Circuitsmentioning
confidence: 80%
“…; Saint‐Cyr, ; Stuesse & Newman, ; Onodera & Hicks, ) and deep cerebellar nuclei (Gonzalo‐Ruiz et al . ; Ruigrok & Voogd, ; Ruigrok & Teune, ), and thus the sensory signals are assumed to be subject to multiple modulation by higher brain regions. These lines of evidence suggest the importance of this network in cerebellar functions.…”
Section: Discussionmentioning
confidence: 99%
“…There are reciprocal connections with the supraoculomotor gray, an area implicated in cerebellar modulation of near-object visual responses (Gonzalo-Ruiz et al, 1990;May et al, 1992). The nucleus of Darkschewitsch, which projects to midline and intralaminar thalamic nuclei (Krout et al, 2002a) and the IGL (Horowitz et al, 2004), is part of the premotor circuitry controlling eyelid responses (Morcuende et al, 2002).…”
Section: Visuomotor System Connectionsmentioning
confidence: 99%